From the environment into the biomass: microplastic uptake in a protected lamprey species. (15th April 2023) - Rendell-Bhatti, Flora; Bull, Colin; Cross, Richard; Cox, Ruairidh; Adediran, Gbotemi A.; Lahive, Elma
Abstract: The relationship between the ubiquitous presence of microplastics in the environment and exposure of biota needs to be better understood, particularly for vulnerable species and their habitats. In this study, we address the presence of microplastics in the riverine habitat of a threatened lamprey species ( Lampetra sp. ), both in habitats with protective interventions in place (designated as Special Areas of Conservation), and those without these protective interventions. By sampling both riverbed sediments and larval lamprey, we provide a direct comparison of the microplastic loadings in both, and insights into how knowledge of sediment loadings might predict biological uptake. Microplastic particles, analysed using micro-Fourier transform infrared (μFTIR) spectroscopy, were detected in all samples of lamprey larvae and paired sediment, ranging in abundance from 1.00 to 27.47 particles g −1 in dry lamprey gastrointestinal tract (GIT) tissue, and 0.40 to 105.41 particles g −1 in dry sediment. The most urbanised catchment exhibited the highest average microplastic particle count in both lamprey and sediment. Across sites, the microplastic abundance in lamprey GIT tissue was not correlated with that of the surrounding sediment, suggesting that either specific polymer types are retained or other factors such as larvae residence time within sediment patches may influence biological uptake. The most encountered polymer types in lamprey from their immediate habitat were polyurethane, polyamide, and cellulose acetate. To the best of our knowledge, this is the first study to document microplastic contamination of larval lamprey in-situ, contributing another potential stressor to the population status of a vulnerable species. This highlights where further research on the impacts of plastic contamination of freshwater environments is needed to aid conservation management of this ecologically important species. Graphical abstract: Image 1 Highlights: Microplastics were identified in protected lamprey and sediment habitat. 1–27 and 0.4–105 particles g −1 were recorded in dry lamprey and sediment samples. Microplastic contamination was present at all sites. Polyurethane was the most abundant polymer type in lamprey larvae. Microplastic load and polymer type are distinct between sites. Abstract : Capsule: Abundance of microplastics detected in gastrointestinal tract tissue from larval lamprey does not correlate with the abundance in their surrounding riverine sediment habitats.